Close of Play President, Prince, and Cricket. - Walcott, William (Black Rose Books, 2020)
"This book is a fascinating journey into the world of global sociopolitical life and the curiosities of language embedded in cricket and political play, both of which constitute enormous sectors within a multibillion dollar "sticky wicket" of transnational capitalism"--